Bioprospecting of Indonesian red seaweeds Gracilaria edulis and Pterocladiella sp. 4: anti-vibrio activity and chemical composition - Dewi Sri Kurnia; Noer Kasanah (Applied Phycology)
Vibriosis is one of the major infectious diseases in aquaculture and a new threat to human health. The increasing resistance of Vibrio spp. to existing antibiotics has driven the search for new anti-vibrio compounds from marine natural products. Red seaweeds (Rhodophyta) are one of the potential sources of anti-vibrio bioactives. The objectives of this study were to investigate and identify chemical constituents of Gracilaria edulis and Pterocladiella sp. 4 and to evaluate their potential against Vibrio harveyi, V. parahaemolyticus and V. alginolyticus. Species identification for the red seaweeds was based on DNA barcoding of the COI gene and the cox 2–3 spacer as G. edulis and Pterocladiella sp. 4 in GenBank. The seaweeds were extracted using ethyl acetate and anti-vibrio activity against V. harveyi, V. parahaemolyticus and V. alginolyticus was tested by bioautography and microtitre plate assays. The chemical constituents were identified using gas chromatography coupled to mass spectrometry (GC-MS) and liquid chromatography coupled to mass spectrometry (LC-MS). Extracts of both G.edulis and Pterocladiella sp. 4 have potential anti-vibrio activity with minimum inhibitory concentrations of 0.625–5 mg ml‒1. GC-MS showed that the fatty acids palmitic acid and its derivatives are the main components. The bioassay of palmitic acid and stearic acid confirmed its activity against Vibrio spp. Dereplication of LC-MS/MS analysis indicated the presence of macrolides and furanyl compounds in the extract of G. edulis.